Analysis of synergistic stator permanent magnet machine with the synergies of flux-switching and flux-reversal effects - Cai, Shun (2022)
Dual permanent magnet (PM) machines have attracted numerous interests due to the high torque density and compact volume. This paper investigates a synergistic PM machines with the synergies of flux switching and flux reversal effects. The flux-reversal and flux-switching PM flux paths circulate from two sides of the split teeth separately, which avoid the over-saturation with dual PM excitations. The preferred stator and rotor pole number is derived from a simplified analytical model and the influence of leading parameters is analyzed as design guidelines. Furthermore, the synergistic stator PM machine is optimized and compared with flux-switching PM (FSPM) machines. It is revealed that the synergistic stator PM machine exhibits ~20%, ~10%, and ~17% higher torque density than conventional FSPM machine, C-core FSPM machine, and E-core FSPM machine, respectively. Besides, good flux weakening capability is achieved with a larger inductance than conventional FSPM machine, and higher efficiency is obtained at both low-speed and high-speed operations. Finally, an experimental prototype is fabricated to validate the proposed concepts.